Hubungan Peran Penyuluh Pertanian Dengan Produktivitas Bawang Merah Di Desa Babuin Kecamatan Kolbano Kabupatentimor Tengah Selatan - Magang, Yesyuru Eka; Bernadina, Lika; Bureni, Eman Nevianus; Hendrik, Ernantje (Undana Press, 2024)
This research was conducted on Shallot Farmers in Babuin Village, Kolbano District, South Central Timor Regency from October to November 2023. The purpose of the study is to find out: 1) Productivity of Shallots. 2) The role of agricultural extension workers in increasing shallot productivity. 3) The Relationship between the Role of Agricultural Extension Workers and Shallot Productivity. The data collection methods used are observation, interview and documentation methods. The data analysis method used is the Likert scale method. The results of the study show that: (1) The productivity of shallots shows that the average productivity level at the research site is 5.53 Tons/Ha. The highest percentage of 67.65% was in the interval of >5.53 Tons/Ha and the lowest percentage of 32.35% was in the interval of <5.53 Tons/Ha. (2) The average score of the role of agricultural extension workers is 2.77. The percentage of achieving the maximum score from this score is 92.48%. Thus, the role of agricultural extension workers is in the category of very important. (3) The relationship between the role of agricultural extension workers and the productivity of shallots was obtained with a tcal value of 0.477, and the ttable obtained a value of 0.239. The tcal value is larger than the table, so it is concluded that there is a significant difference between the role of agricultural extension workers and the productivity of shallots.